Molecular characterization of extended spectrum β-lactamase (ESBL) producing Shigella species isolated from patients with bacillary dysentery in Iraq - Abd Al-Rahman, Thanaa R.; Belal, Sabah A.; Jasim, Kifah A. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Extended-spectrum β-lactamases (ESBLs), including cefotaximases (CTX-M), mediate resistance to extended spectrum cephalosporins and significantly compromise the treatment tools for Shigellosis. Objective: To determine the ESBLs production by Shigella spp. and its role in the resistance to third generation cephalosporins and to determine the occurrence of plasmid- borne blaCTX genes in ESBLS Shigella isolates by Multiplex PCR. Methods: Susceptibility of 59 clinical Shigella isolates was tested by disk diffusion method to six antimicrobial agents. Presence of ESBLs was established by the combination disk method. Minimum inhibitory concentration of β-lactams was determined by agar dilution method for resistant isolates, and then ESBL producers were subjected to plasmid extraction and PCR experiments. Results: Overall isolates had high rate of resistance to Ampicillin (84.7%), Tetracycline (84.7%), Co-trimoxazole(72.9%) and Cefotaxime(69.5%). Moderate to Ceftriaxone (52.5%) and low rate of resistance to Ceftazidime(30.5%). The MIC value of resistant isolates of S. sonnei and S. flexneri for CTX and CRO ranged from (64-512 μg/ml) for both, and (32-256 μg/ml) for CAZ, whereas S. dysenteriae exhibit only high level resistance MIC (256 μg/ml) for CTX, low level resistance (64 μg/ml) for CRO and complete susceptibility to CAZ. 31 of 41 (75.6 %) of Shigella spp. were β-lactamase producers, of these (82.6%) were S. flexneri, (68.8%) S. sonnei, and one S. dysenteriae isolate. The results of PCR amplification of bla CTX gene groups showed that blaCTX-M genes were identified in (74.19%) ESBLs isolates distributed as 14(45.16%) S.flexneri isolates, 9(29.03%) S. sonnei, while no gene was detected in ESBLs S. dysenteriae isolate. The prevalence of bla CTX-M I, bla CTX-M II (TOHO 1) and blaCTX-M III, were ( 54.8%, 16.1% and 3.2% ) respectively. Non of the isolates carried more than one type. Conclusion: The occurrence of plasmid- borne blaCTX genes in ESBLS Shigella isolates are increasing in Iraq with co-resistance to some other classes of antibiotics